Recombinant antigen P29 of Echinococcus granulosus induces Th1, Tc1, and Th17 cell immune responses in sheep - Yang, Jihui; Zhao, Yinqi; Fu, Yong; Lv, Yongxue; Zhu, Yazhou; Zhu, Mingxing; Zhao, Jiaqing; Wang, Yana; Wu, Changyou; Zhao, Wei (Frontiers in Immunology, 2023)
Echinococcosis is a common human and animal parasitic disease that seriously endangers human health and animal husbandry. Although studies have been conducted on vaccines for echinococcosis, to date, there is no human vaccine available for use. One of the main reasons for this is the lack of in-depth research on basic immunization with vaccines. Our previous results confirmed that recombinant antigen P29 (rEg.P29) induced more than 90% immune protection in both mice and sheep, but data on its induction of sheep-associated cellular immune responses are lacking. In this study, we investigated the changes in CD4+ T cells, CD8+ T cells, and antigen-specific cytokines IFN-γ, IL-4, and IL-17A after rEg.P29 immunization using enzyme-linked immunospot assay (ELISPOT), enzyme-linked immunosorbent assay (ELISA), and flow cytometry to investigate the cellular immune response induced by rEg.P29 in sheep. It was found that rEg.P29 immunization did not affect the percentage of CD4+ and CD8+ T cells in peripheral blood mononuclear cells (PBMCs), and was able to stimulate the proliferation of CD4+ and CD8+ T cells after immunization in vitro. Importantly, the results of both ELISPOT and ELISA showed that rEg.P29 can induce the production of the specific cytokines IFN-γ and IL-17A, and flow cytometry verified that rEg.P29 can induce the expression of IFN-γ in CD4+ and CD8+ T cells and IL-17A in CD4+ T cells; however, no IL-4 expression was observed. These results indicate that rEg.P29 can induce Th1, Th17, and Tc1 cellular immune responses in sheep against echinococcosis infection, providing theoretical support for the translation of rEg.P29 vaccine applications.